The Benefits and Limitations of Digital Tools to Retrieve the Emotions of Nineteenth-Century Readers of Philosophy from Manuscript Letters - Ouvry-Vial, Brigitte; Richard, Nathalie (Knygotyra, 2022)
This article discusses the limitations and benefits of resorting to digital tools and research methodology to explore nineteenth-century manuscript letters, written by readers to the French philosopher Victor Cousin, and to increase our understanding of how ordinary readers responded to philosophy at the time. More broadly, it examines the potential assets of the annotation interface developed in the Reading Europe Advance Data Investigation Tool (READ-IT https://readit-project.eu/ 2018–2021), a collaborative research project focusing on regenerating lost connections about the cultural heritage of reading from large volumes of highly-diverse eighteenth- to twenty-first-century sources in multiple languages. The case study describes challenges raised by attempts to detect and classify differences between female and male philosophical reading experiences as well as emotional responses, something which is largely under-explored. Along the way it provides reflexive as well as epistemological insights into the promises of big data for research on cultural history and literary archives and the current state of knowledge on emotions.